Effects of silver nanoparticles on human and rat embryonic neural stem cells - Liu, Fang; Mahmood, Meena; Xu, Yang; Watanabe, Fumiya; Biris, Alexandru S.; Hansen, Deborah K.; Inselman, Amy; Casciano, Daniel; Patterson, Tucker A.; Paule, Merle G.; Slikker, William; Wang, Cheng (Frontiers in Neuroscience, 2015)
Silver nano-particles (Ag-NPs) are becoming increasingly prevalent in consumer products as antibacterial agents. The increased use of Ag NP-enhanced products will almost certainly increase environmental silver levels, resulting in increased exposures and the potential for increased adverse reactions including neurotoxic effects. In the present study, embryonic neural stem cells (NSCs) from human and rat fetuses (gestational day-16) were used to determine whether Ag-NPs are capable of causing developmental neurotoxicity. The NSCs were cultured in serum free medium supplemented with appropriate growth factors. On the eighth day in vitro (DIV 8), the cells were exposed to Ag-NPs at concentrations of 1, 5, 10, and 20 µg/ml for 24 hours. The cultured cells then were characterized by NSC markers including nestin and SOX2 and a variety of assays were utilized to determine the effects of Ag-NPs on NSC proliferation and viability and the underlying mechanisms associated with these effects. The results indicate that mitochondrial viability (MTT metabolism) was substantially attenuated and LDH release was increased significantly in a dose-dependent manner. Ag-NPs-induced neurotoxicity was further confirmed by up-regulated Bax protein expression, an increased number of TUNEL-positively stained cells, and elevated reactive oxygen species (ROS). NSC proliferation was also significantly decreased by Ag-NPs. Co-administration of acetyl-L-carnitine, an antioxidant agent, effectively blocked the adverse effects associated with Ag-NP exposure.